2020
DOI: 10.3390/ijms21124457
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and Photosynthetic Responses of Pod Walls in Alfalfa to Drought Stress

Abstract: Increasing photosynthetic ability as a whole is essential for acquiring higher crop yields. Nonleaf green organs (NLGOs) make important contributions to photosynthate formation, especially under stress conditions. However, there is little information on the pod wall in legume forage related to seed development and yield. This experiment is designed for alfalfa (Medicago sativa) under drought stress to explore the photosynthetic responses of pod walls after 5, 10, 15, and 20 days of pollination (DAP5, DAP10, DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Stress has been shown to increase the expression of C 4 rather than C 3 specific genes in non-leaf plant systems. For example, this has been reported in alfalfa pod walls [48] and wheat [2]. This suggests that selection of plants with enhanced levels of expression of these traits [70] may be useful in breeding plants with greater stress tolerance.…”
Section: Importance and Function Of Non-leaf Photosynthesismentioning
confidence: 82%
“…Stress has been shown to increase the expression of C 4 rather than C 3 specific genes in non-leaf plant systems. For example, this has been reported in alfalfa pod walls [48] and wheat [2]. This suggests that selection of plants with enhanced levels of expression of these traits [70] may be useful in breeding plants with greater stress tolerance.…”
Section: Importance and Function Of Non-leaf Photosynthesismentioning
confidence: 82%
“…The drought stress could significantly induce the activities of NADP-MDH, NADP-ME, NAD-ME, and PPDK in non-leaf organs (Figure 4). The previous studies reported that in non-leaf organs, the PEPC activity was significantly higher than in leaves and was induced under drought stress (Imaizumi et al, 1990;Jia et al, 2015;Zhang, 2019;Wang et al, 2020). The PEP in non-leaf organs was considered to have the possibility to recapture the respired CO 2 in the dark reaction (Singal et al, 1986).…”
Section: Changes In Photosynthetic Enzyme Activities In Non-leaf Organsmentioning
confidence: 99%
“…However, when leaf photosynthesis is potentially limited, carbohydrate partitioning is shifted from pod walls toward seeds [9,10]. Several lines of evidence have demonstrated that the legume pod wall can photosynthesize and makes an important contribution to seed yield in species, including alfalfa (Medicago sativa) [11], chickpea (Cicer arietinum) [12], soybean (Glycine max) [13], and lentil (Lens culinaris L.) [14]. Thus, the physiological responses to drought in the pod wall may be due to the adjustment of metabolism to maintain homeostasis and seed filling.…”
Section: Introductionmentioning
confidence: 99%